DEVELOPING INQUIRY LEARNING MODEL-BASED ENGLISH INSTRUCTIONAL MATERIALS FOR THE SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Putri Nurul Ifani; Sitti Nurpahmi; Djuwairiah Ahmad (Universitas islam Negeri Alauddin Makassar, 2020)
This research aimed at developing instructional English materials for the students of the seventh grade especially in basic competencies 3.4 and 4.4 at MTs Madani Pao-pao based on 2013 curriculum supported by using inquiry learning model and using the concept of HOTS. The research design is Research and Development (R&D )with the combination of ADDIE model. The procedures included analyzing materials needed by spreading questionnaire to the students and analyzing the basic competencies, designing a blueprint of materials and the instructional materials, and validating the material by the expert. There were 146 students as the respondents, teachers, and experts. The instruments used in this research were the documents, questionnaires, and validation checklist. There were three systematic aspects : materials Systematic Organization, Systematic English Teaching and Systematic Content of English. Therefore, the result indicated that based on experts judgment, the developed basic competency 3.4 and 4.4 were applicable to be taught at the seventh grade students of Junior High School.